The impact of strategic jump bidding in residential English auctions. Issue 3 (2nd July 2020) - Khazal, Aras; Sønstebø, Ole Jakob; Olaussen, Jon Olaf; Oust, Are
ABSTRACT: In the Norwegian real estate market, used dwellings are normally sold through an auction process similar to the standard English (open ascending-bid) auction. Using survey results (N = 1, 803), we define jump bids and investigate the motivations behind the use of such strategies. We find that most bidders tend to consider intimidation and signalling as the main motivations for applying a jump-bidding strategy, and intimidation strategies applied by competing bidders appear to be an important reason for bidders withdrawing early from an auction. We also use a sample of 1, 142 auction journals and find that, on average, auctions containing jump bids achieve 2.8–9.3 percent higher price premiums compared to strictly straightforward-bidding auctions. The premium is higher when the intimidation strategy fails and competing bidders counter with jump bids. Additionally, this paper provides evidence that jump bids are usually placed at the earliest stage of the auction and have a stronger intimidation effect the earlier they are placed, despite having an overall positive effect on the premium. The results are robust to different valuation approaches and omitted variable bias controls. Our findings have important implications for sellers and buyers in auction settings, and for regulators of auction processes.